Developing a Slow-Release Permanganate Composite for Degrading Aquaculture Antibiotics - Chainarong Sakulthaew; Chanat Chokejaroenrat; Sidaporn Panya; Apisit Songsasen; Kitipong Poomipuen; Saksit Imman; Nopparat Suriyachai; Torpong Kreetachat; Steve Comfort (MDPI AG, 2023)
Copious use of antibiotics in aquaculture farming systems has resulted in surface water contamination in some countries. Our objective was to develop a slow-release oxidant that could be used in situ to reduce antibiotic concentrations in discharges from aquaculture lagoons. We accomplished this by generating a slow-release permanganate (SR-MnO4−) that was composed of a biodegradable wax and a phosphate-based dispersing agent. Sulfadimethoxine (SDM) and its synergistic antibiotics were used as representative surrogates. Kinetic experiments verified that the antibiotic-MnO4− reactions were first-order with respect to MnO4− and initial antibiotic concentration (second-order rates: 0.056-0.128 s−1 M−1). A series of batch experiments showed that solution pH, water matrices, and humic acids impacted SDM degradation efficiency. Degradation plateaus were observed in the presence of humic acids (>20 mgL−1), which caused greater MnO2 production. A mixture of KMnO4/beeswax/paraffin (SRB) at a ratio of 11.5:4:1 (w/w) was better for biodegradability and the continual release of MnO4−, but MnO2 formation altered release patterns. Adding tetrapotassium pyrophosphate (TKPP) into the composite resulted in delaying MnO2 aggregation and increased SDM removal efficiency to 90% due to the increased oxidative sites on the MnO2 particle surface. The MnO4− release data fit the Siepmann-Peppas model over the long term (t < 48 d) while a Higuchi model provided a better fit for shorter timeframes (t < 8 d). Our flow-through discharge tank system using SRB with TKPP continually reduced the SDM concentration in both DI water and lagoon wastewater. These results support SRB with TKPP as an effective composite for treating antibiotic residues in aquaculture discharge water.